Comparative dissolution studies of albendazole oral suspensions for veterinary use - González Vidal, Noelia Luján (2013)
Helminth infections are a major health problem mainly in developing countries, and the evidence of emerging resistance to all the major antihelminthics has been recognized in the field of animal husbandry. Albendazole (ABZ) is the most effective broad-spectrum antihelminthic agent. The biggest problem with this drug is its low aqueous solubility, which leads to an erratic availability and great intraindividual variation in the levels reached in different tissues. As with other poorly soluble compounds, the dissolution rate is likely to be contingent on the formulation and may lead to differences in performance among different products available in the market. In previous studies, drastic pharmacokinetic differences were observed among ABZ formulations (oral suspensions) in the Uruguayan market. These samples were evaluated in vitro in terms of ABZ content and dissolution profiles, as well as the effect of increasing agitation speeds on the dissolution rate. The in vitro dissolution rate of formulation A was seriously affected by the increase in agitation speed, and in the case of formulation B, it did not fulfill both essential quality requirements (drug content and dissolution profile). Further studies may be carried out to correlate the suspension quality with its therapeutic effectiveness.